A method for the precise and absolute measurement of microwave chirp rates in cold-atom gravimeters - Huan-Kai Zhang; Ji-Xun Liu; Chang-Wen Liang; Yi-Fei Zhang; Chao Zhou; Shu-Hua Yan; Ling-Xiao Zhu; Jun Yang (AIP Advances)
In a cold-atom gravimeter based on Raman transition, the frequency of Raman lasers is controlled by microwave signals. The accuracy of the chirp rates of the microwave signals directly influences the accuracy of gravity measurements. This study presents a methodology for the precise and absolute measurement of the chirp rate of microwave signals utilizing commercial instruments, achieving a measurement precision superior to 1 mHz/s. To validate this method, we measured the chirp rate of a customized microwave source. The difference between the measured chirp rate and its set value was determined to be −4.56 ± 0.16 mHz/s, which corresponds to a gravity measurement error of −0.17 ± 0.01 μGal. Employing it as a reference source, we measured the chirp rate of the electro-optic modulator drive signal in a cold-atom gravimeter. The result indicates that the gravity measured by this gravimeter is 67 ± 17 μGal higher when the internal reference is employed for its microwave source than when an external reference is employed. The actual deviation as determined by the gravity measurement is 54.4 ± 3.0 μGal, which aligns well with our assessment result. The proposed method for the precise measurement of chirp rates no longer requires an absolutely accurate reference source and offers a novel approach for evaluating the chirp-rate-related measurement error of cold-atom gravimeters.